Opportunities and Challenges for Individual Small Businesses - Syahrida Syahrida; Junaidi Arif (International Journal of Southeast Asian Studies (IJSAS), 2022)
Integration of the rules of the Job Creation Law in terms of encouraging the growth of micro-enterprises in the form of Individual Limited Liability Companies to improve the economy. The type of research used is empirical normative legal research that focuses on field research to obtain primary data, and literature research that serves to complement and support data obtained in the field. The results showed the inequality of perceptions regarding the categories of micro-enterprises and small businesses, because the difference in handling authority between Small Businesses is in the Department of Industry and Trade, while for Micro-Enterprises the authority is in the Office of Cooperatives, Micro Enterprises and Manpower, so there is a need for regulatory integration in a draft regional regulation, to increase economic growth, especially in providing capital assistance by banking institutions for Individual Limited Liability Company Micro Enterprises without the condition of having to attach a deed of establishment of an Individual Limited Liability Company, because these conditions do not exist in the Job Creation Law.